Applying Design Science Research to Develop a Process Reference Model for IT Workforce Outsourcing: Preliminary Findings - Simões, Carlos; Santos, Gleison (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3330, 2024)
IT organizations in Brazil increasingly use workforce outsourcing, and it has become a strategic choice, facilitating innovation, flexibility, and effectiveness in the process execution. This paper presents how we created the Process Reference Model for IT Workforce Outsourcing (MR-TFT) using an approach based on Design Science Research. MR-TFT considers typical and critical aspects of IT workforce outsourcing – for both contractors and suppliers – identified from interviews with industry professionals and a mapping study. It adapts important concepts of software engineering to support workforce outsourcing practices. MR-TFT covers the entire life cycle of providing this type of service, including defining the strategy, managing the agreement between the parties, implementing the outsourcing, evaluating the performance and quality of services performed by the outsourced workforce, and continuously improving the related processes. We also present results from a case study in the context of diagnosing the outsourcing practices in which the model was considered useful and viable.